Association Between Nonrestorative Sleep and Risk of Diabetes: A Cross-Sectional Study. Issue 6 (2nd November 2017) - Okamoto, Masaki; Kobayashi, Yasuki; Nakamura, Fumiaki; Musha, Terunaga
Abstract : Although insufficient sleep or poor sleep quality has been reported to be associated with the development of type 2 diabetes, the relation of type 2 diabetes with nonrestorative sleep (NRS), a subjective feeling, has been overlooked. We used a large-scale medical checkup database to investigate whether there is a cross-sectional association between NRS and type 2 diabetes risk in Japanese individuals. We extracted data for 14, 476 individuals who were not receiving therapeutic drugs for diabetes. About 36.8% of individuals were identified as having NRS. In a multiple logistic regression analysis, NRS was significantly associated with the risk of developing diabetes. Thus, this line of research may have implications for diabetes prevention.